1985
DOI: 10.1111/j.1365-2125.1985.tb02664.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of propranolol and digoxin on the acute vascular responses to frusemide in normal man.

Abstract: 1 To examine the importance of acute frusemide-induced renin release in the production of the acute peripheral venous and arterial responses to frusemide in man, the effects of two drugs, previously described as inhibitors of acute frusemide-induced renin release, propranolol and digoxin, were examined. 2 Propranolol abolished the acute increases in venous capacitance and blood pressure and attenuated the increases in forearm vascular resistance produced by frusemide. The acute increases in plasma renin activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The early rise in renin activity, seen in the present study 10 min after frusemide, has been widely reported (Brater et al, 1985;Frolich et al, 1976;Johnston et al, 1985Johnston et al, , 1986Mackay et al, 1984;Passmore et al, 1989;Riley et al, 1985) and is not related to natriuresis but may coincide in some way with the increment in renal blood flow. While the nature of this response is not clear, most of the available evidence suggests that prostaglandins act as mediators, since the rise in renin activity following frusemide is consistently blocked by indomethacin (Frolich et al, 1976;Mackay et al, 1984;Passmore et al, 1989) and ibuprofen (Brater et al, 1985;Passmore et al, 1989;Riley et al, 1985).…”
Section: Discussionsupporting
confidence: 77%
“…The early rise in renin activity, seen in the present study 10 min after frusemide, has been widely reported (Brater et al, 1985;Frolich et al, 1976;Johnston et al, 1985Johnston et al, , 1986Mackay et al, 1984;Passmore et al, 1989;Riley et al, 1985) and is not related to natriuresis but may coincide in some way with the increment in renal blood flow. While the nature of this response is not clear, most of the available evidence suggests that prostaglandins act as mediators, since the rise in renin activity following frusemide is consistently blocked by indomethacin (Frolich et al, 1976;Mackay et al, 1984;Passmore et al, 1989) and ibuprofen (Brater et al, 1985;Passmore et al, 1989;Riley et al, 1985).…”
Section: Discussionsupporting
confidence: 77%
“…An early increase in renin activity, which was evident from 10 min after frusemide, has been seen in many studies (Frolich et al, 1976;Mackay et al, 1984;Johnston et al, 1985Johnston et al, , 1986Riley et al, 1985) and is unrelated to natriuresis. The exact nature of this response remains unclear, but a weight of evidence suggests that prostaglandins are involved, since the increase in renin activity following frusemide is consistently blocked by the prostaglandin inhibitors indomethacin (Frolich et al, 1976;Weber et al, 1977;Mackay et al, 1984) and ibuprofen (Riley et al, 1985).…”
Section: Discussionmentioning
confidence: 68%
“…We have previously demonstrated that the acute peripheral vascular effects of intravenous frusemide on venous capacitance, peripheral blood flow and blood pressure only occur when the kidney is in a salt retaining state and when frusemide gives rise to acute renin release (Johnston et al, 1983a(Johnston et al, , b, 1985. We postulated that the peripheral arterial constrictor effects occurred secondary to angiotensin II formation while the venous effects were due to the release of vasodilatory substancesprostaglandins, kinins, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this hypothesis are the observations that indomethacin, salt overloading and propranolol prevent acute frusemide stimulated renin release and attenuate the peripheral vascular responses (Johnston et al, 1983a(Johnston et al, , 1985 (Johnston et al, 1983b). The following experiment was therefore undertaken to compare the peripheral venous and arterial effects of intravenous bumetanide and frusemide at comparable diuretic doses and to examine the relationship between these responses and the changes in plasma renin activity.…”
Section: Introductionmentioning
confidence: 99%